2023
DOI: 10.1177/19458924231152331
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cryoablation on Chronic Rhinitis Management: A Systematic Review and Meta-Analysis

Abstract: Background ClariFix for posterior nasal nerve ablation has been approved for use since 2017, and this is the first study attempting to synthesize and assess the efficacy of this new device on the management of chronic rhinitis. Objective The primary objective of this meta-analysis is to assess the efficacy of ClariFix in the symptomatic management of patients with chronic rhinitis. The main outcome measure is the mean difference in the reflective total nasal symptom score (rTNSS). Methods A systematic search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The total rTNSS improved from baseline to all time points and the responder rate was 80% at 12 months. These findings are consistent with findings of our device and other devices for rhinitis 4,15,16 . Confirming chronic rhinitis specific quality of life improvement, the total mini RQLQ score and all 5 domains significantly improved over baseline and the 12‐month MCID rate was 86%.…”
Section: Discussionsupporting
confidence: 91%
“…The total rTNSS improved from baseline to all time points and the responder rate was 80% at 12 months. These findings are consistent with findings of our device and other devices for rhinitis 4,15,16 . Confirming chronic rhinitis specific quality of life improvement, the total mini RQLQ score and all 5 domains significantly improved over baseline and the 12‐month MCID rate was 86%.…”
Section: Discussionsupporting
confidence: 91%
“…However, “chronic rhinitis”, a previously reported indication, is an ambiguous definition. Two reviews were reported, but neither provided a clear definition of chronic rhinitis, and all included articles with various rhinitis evaluation criteria 25,26 . Young et al 26 provided data up to 3 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews were reported, but neither provided a clear definition of chronic rhinitis, and all included articles with various rhinitis evaluation criteria 25,26 . Young et al 26 provided data up to 3 months after treatment. Pooled rTNSS MD from baseline to 1 and 3 months postoperatively was found to be −3.48 points (95% CI: −3.73 to−3.23 and −3.50 [95%] CI: −3.71 to −3.29), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryoablation of the posterior nasal nerve to treat chronic rhinitis became more available in 2017 following the introduction of the Clarifix device which offered an alternative to more traditional surgical treatments such as vidian neurectomy. Young et al 3 present a systematic review and meta-analysis examine the efficacy of cryoablation for chronic rhinitis and suggest that their findings indicate that it is an effective treatment modality for the ailment.…”
mentioning
confidence: 99%